Scope of services provided to childhood cancer patients by the Brazilian Pediatric Palliative Care Network - Ferreira, Esther Angélica Luiz; Valete, Cristina Ortiz Sobrinho; Barbosa, Silvia Maria de Macedo; Costa, Graziela de Araujo; Molinari, Poliana Cristina Carmona; de Castro, Ana Cristina Pugliese; Iglesias, Simone Brasil de Oliveira; Sarracini, Maycon Rodrigo; Reiff, Rodrigo Bezerra de Menezes; Bruno, Cristina Helena; Gómez-Cantarino, Maria Sagrario; Ullán, Ana María (Frontiers in Oncology, 2024)
Introduction Brazil is a developing and an Upper Middle Income, categorized by the World Bank. Therefore, it is a country that needs a special vision for children with oncological diseases who require Pediatric Palliative Care. This study aimed to understand the specificities of services that provide oncology services in comparison to those that do not provide oncological care. Methods This is a descriptive, cross-sectional, and online survey study. A questionnaire was created by a multidisciplinary group of leaders from the Brazilian Pediatric Palliative Care Network and then the survey was distributed using a snowball strategy. Results Of the 90 services that answered the questionnaire, 40 (44.4%) attended oncologic patients. The Southeast represented most of the services (57.57%), followed by the Northeast, with 18.89% (17 services), the South with 12.22% (11 services), and the Center West with 8.89% (8 services). No differences were observed in access to opioid prescriptions between the services. It was observed that those services that attended oncologic patients had a tendency to dedicate more time to Pediatric Palliative Care. Discussion The distribution of services that cover oncology and those that do not, are similar in the different regions of Brazil. In Brazil, there are difficulties in accessing opioids in pediatrics: access to opioid prescriptions without differences revealed that even pediatric oncologists might have difficulty with this prescription, and this should improve. It is concluded that education in Pediatric Palliative Care is the key to improvements in the area.